The art of theft - Thomas, Sherry (Sherry M.) (Thomas, Sherry (Sherry M.). Lady Sherlock series., 2019)
"As "Sherlock Holmes, consulting detective," Charlotte Holmes has solved murders and found missing individuals. But she has never stolen a priceless artwork--or rather, made away with the secrets hidden behind a much-coveted canvas. But Mrs. Watson is desperate to help her old friend recover those secrets and Charlotte finds herself involved in a fever-paced scheme to infiltrate a glamorous Yuletide ball where the painting is one handshake away from being sold and the secrets a bare breath from exposure. Her dear friend Lord Ingram, her sister Livia, Livia's admirer Stephen Marbleton--everyone pitches in to help and everyone has a grand time. But nothing about this adventure is what it seems and disaster is biding time on the grounds of a glittering French chateau, waiting only for Charlotte to make a single mistake."--